Assisting Russia's Transition : An Unprecedented Challenge - Zanini, Gianni (Washington, DC: World Bank, 2013)
The Country Assistance Evaluation (CAE) for Russia, covering the period 1992-2001, showed disappointing, but improving results for the Bank's activities in the Russian Federation. Despite unsatisfactory ratings during 1992-98, with only modest institutional development impacts, the Operations Evaluation Department (OED) rated the outcome satisfactory for the period 1998-01, and institutional development impacts as substantial. This paper reviews the decade of rapid political, and economic transformation, where obstacles to reform had to be surmounted, namely, state-owned institutions' need to focus on regulation and oversight; an economic structure more focused on comparative advantage; production and distribution systems' need to undergo organizational, and structural changes; while the newly created financial sector struggled through regulation, amidst a weak authority, and complex federal system. Yet, no major policy reversal occurred, and economic recovery is in place. The paper then examines from investment lending to the adjustment lending, with an improved portfolio performance as of 1999, where the question remains on the resilience of achievements to external shocks, particularly the drop of oil prices and other export commodities. Recommendations include assistance for reform, focused on further social consensus, with emphasis on public sector management, legal and judicial reform, investment and business climate, pension reform and labor market performance.